1991
DOI: 10.1002/jor.1100090417
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of bone loss during disuse by pulsed electromagnetic fields

Abstract: The effect of pulsed electromagnetic fields (PEMFs) on bone loss associated with disuse was investigated by applying 1.5 Hz repetitions of 30 ms bursts of asymmetric pulses, varying from +2.5 to -135 mV, to bones deprived of their normal functional loading. The proximal portion of one fibula in each of a group of ovariectomised adult female beagle dogs was isolated from functional loading in vivo by proximal and distal osteotomies. Comparison of these prepared bones with their intact contralateral controls aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Several experimental studies have demonstrated that PEMF stimulation could prevent bone mass loss and microarchitecture deterioration, and improve bone's biomechanical properties in various animal models of osteoporosis [16][17][18]. This efficiency of PEMF was further confirmed by numerous clinical investigations [19,20].…”
Section: Introductionmentioning
confidence: 59%
“…Several experimental studies have demonstrated that PEMF stimulation could prevent bone mass loss and microarchitecture deterioration, and improve bone's biomechanical properties in various animal models of osteoporosis [16][17][18]. This efficiency of PEMF was further confirmed by numerous clinical investigations [19,20].…”
Section: Introductionmentioning
confidence: 59%
“…Mishima [1988] found pulse burst waves at a positive amplitude of 25 mV, burst width of 4.2 ms, pulse width of 230 ms, and repetition rate of 12 Hz to be effective in preventing osteoporosis caused by bilateral ovariectomy and right sciatic neurectomy in rats. Skerry et al [1991] found that pulse burst with burst width of 30 ms, repetition rate of 1.5 Hz, and positive amplitude of 2.5 mV had the capability to inhibit the bone loss in disuse osteoporosis. Rubin et al [1989] used a turkey model of disuse osteoporosis to show that pulse burst with 30 ms bursts at a repetition rate of 1.5 Hz and each burst containing 120 repetitions of an asymmetrical pulse were effective in preventing bone loss by regulating cortical bone remodeling.…”
Section: Discussionmentioning
confidence: 98%
“…Given this background it would be natural to ask whether PEMFs could have a benefit in preserving bone mass in situations that lead to osteopenia, such as disuse. There have been a number of experiments in animal models of osteopenia that support such a beneficial effect after mechanical unloading [Bassett et al, 1979;Cruess and Bassett, 1983;Rubin et al, 1989;Skerry et al, 1991;Shen and Zhao, 2010] or ovariectomy [Zati et al, 1993;Bilotta et al, 1994;Chang and Chang, 2003]. On the other hand, we found only a few reports of the attempt to improve bone density in humans using low frequency or PEMFs in osteoporosis [Tabrah et al, 1990[Tabrah et al, , 1998Bilotta et al, 1994;Giordano et al, 2001], or in other situations [Eyres et al, 1996;Garland et al, 1999] but they were generally small and/or not well controlled.…”
Section: Introductionmentioning
confidence: 96%